Wingless-Type MMTV Integration Site Family Member 5a Is a Key Secreted Islet Stellate Cell-Derived Product that Regulates Islet Function - Wei Xu; Jun Liang; H. F. Geng; Jun Lu; Rui Li; X. L. Wang; Qian Lv; Ying Liu; Jie Wang; X. K. Liu; Peter M. Jones; Zl Sun (International Journal of Endocrinology)
Background. Emerging evidence suggests that T2DM is attributable to the dysfunction of β-cells and the activation of islet stellate cells (ISCs). The wingless-type MMTV integration site family member 5a (Wnt5a)/frizzled 5 (Fzd5) signalling pathway might take part in this process. Our study is aimed at defining the status of ISCs during β-cell insulin secretion homeostasis by determining the role of the Wnt5a protein in the regulation of insulin production. We examined the effects of the status of ISCs on β-cell insulin secretion in normoglycemic db/m and hyperglycaemic db/db mice. Methods. iTRAQ protein screening and RNA interference were used to determine novel ISC-derived secretory products that may use other mechanisms to influence the function of islets. Results. We showed a significant reduction in insulin secretion by β-cells in vitro when they were cocultured with db/db ISCs compared to when they were cocultured with ISCs isolated from normoglycemic db/m mice; in addition, both Wnt5a and its receptor Fzd5 were more highly expressed by quiescent ISCs than by activated db/db ISCs. Treatment with exogenous Wnt5a increased the secretion of insulin in association with the deactivation of ISCs. Conclusion. Our observations revealed that the Wnt5a protein is a key effector of ISC-mediated improvement in islet function.